The Methodologies and Main Challenges of Assessment the Multi-Hazard Interaction and Risk Management Associated with Roads Infrastructures and Dam Safety: A Review - Al Hudaib, Hayder Thabit; P. Ray, Richard (International Journal of Integrated Engineering, 2023)
The idea of multi-hazard interactions and risk assessment, particularly in relation to both natural hazards and hazards triggered by anthropogenic processes, has been widely used, especially in recent decades. Numerous areas worldwide, as well as various sectors, face exposure to multiple hazards. These hazards encompass natural phenomena like floods, earthquakes, hurricanes, and more. In comparison, the human-induced or anthropogenic processes associated with infrastructure development, along with other potential human activities such as, land and cover use change, contribute to the overall hazard landscape. Both natural hazards and anthropogenic-induced directly led to infrastructure collapse and loss of functionality with other consequences for human lives, economy, beside the environment impacts. Limited studies have been conducted on the implementation of the comprehensive multi-hazard interaction approach, which is globally or regionally required, along with detailed studies on the interaction between different multi-hazard sources and their interrelationships in short-term or long-term scenarios. The current research aims to review previous literature and studies on the multi-hazard interaction approach, methodologies of visualization and classification, as well as explores the potential of multi-hazard associated with road networks, infrastructures, and dams. The research utilizes simulation various models and tools such as, Geographic Information System (GIS) beside Remote Sensing (Rs) techniques. The current study concludes that using multi-hazard maps, hazard matrix, and fragility curves represents highly valuable and very useful and flexible tools for implementing and visualization hot spot areas exposure by multi-hazard consequences and vulnerability analysis for short and long-term scenarios. In addition, the current review highlighted for development a holistic conceptual framework for multi-hazard and risk assessment associated with hydraulic structures such as dams, road networks and infrastructures with hazard exposure analysis to be used as tools for a decision support system (DSS) in order to develop urban resilience, risk management and hazard mitigations.